2015
DOI: 10.2116/analsci.31.677
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Circulating Current on the Propagation of the Change in Membrane Potential

Abstract: The TFPB -salts of bis(triphenylphosphoranylidene)ammonium (BTPPATFPB) and tetraethylammonium (TEATFPB) were obtained by mixing a methanol solution of NaTFPB with a methanol solution of BTPPACl (Sigma-Aldrich Co.) and TEACl The propagation of the change in potential differences across liquid membranes from the potential-sending cell to the potential-receiving cell was investigated by use of a system combined with three liquid membrane cells, which were composed of two aqueous phases and a 1,2-dichloroethane so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…When the surface of the nerve cell is divided into multiple domains, it is difficult to accurately evaluate the membrane potential and membrane current of each domain. Therefore, the authors' group has conducted the interpretation of the propagation of the change in the membrane potential using an electrochemical cell system composed of several liquid-membrane cells which are connected in parallel [17][18][19][20]. It has been clarified that the change in the membrane potential is propagated by the generation of the circulating current through two liquid membrane sites (the potential-sending and potential -1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 receiving sites) and that the magnitude of the circulating current determines the threshold to produce the change in the membrane potential by considering the electroneutrality and the mass-balance of every phase [17,21].…”
Section: Introductionmentioning
confidence: 99%
“…When the surface of the nerve cell is divided into multiple domains, it is difficult to accurately evaluate the membrane potential and membrane current of each domain. Therefore, the authors' group has conducted the interpretation of the propagation of the change in the membrane potential using an electrochemical cell system composed of several liquid-membrane cells which are connected in parallel [17][18][19][20]. It has been clarified that the change in the membrane potential is propagated by the generation of the circulating current through two liquid membrane sites (the potential-sending and potential -1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 receiving sites) and that the magnitude of the circulating current determines the threshold to produce the change in the membrane potential by considering the electroneutrality and the mass-balance of every phase [17,21].…”
Section: Introductionmentioning
confidence: 99%
“…We confirmed that the change in the membrane potential was propagated by the generation of the circulating current through two liquid membrane sites (the potential-sending and the potential-receiving sites), and that the magnitude of the circulating current determined the threshold to cause the change in the membrane potential by considering the electroneutrality and the mass-balance. [8][9][10][11] In addition, it has been found that the iR drop generated by the resistor in the electric circuit depresses and slows down the propagation of the change in the membrane potential and that the charging current generated by the capacitor in the electric circuit delays the propagation, analogous to the nerve transmission. 10 In the present study, a new model system of nerve conduction was constructed by the use of some liquid-membrane cells that mimic the function of the K + and Na + channels.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a model system combining multiple liquid-membrane cells has been applied to examine the propagation mechanism of electrical signals within one cell or among multiple cells by the author's group. [18][19][20][21][22][23][24][25][26][27][28] It was proved that propagation of the membrane potential was caused by locally circulating currents in the model neuron composed of several liquid-membrane cells mimicking Na + and K + channels. [24][25][26] The author's group has pointed out that there are serious problems in conventional concepts of nerve conduction as follows.…”
Section: Introductionmentioning
confidence: 99%